Surface Behavior of Aprotic Mixtures: Dimethyl Sulfoxide/Acetonitrile - Rodriguez, Javier (2017)
We present results from molecular dynamics simulations that examine microscopic characteristics of mixtures combining acetonitrile (ACN) and dimethyl sulfoxide (DMSO) at the vicinity of liquid/air and liquid/graphene interfaces. In the former interfaces, our simulations reveal a clear propensity of ACN to lie adjacent to the vapor phase at all concentrations. A simple model based on the consideration of a chemical equilibrium between bulk and surface states was found to be adequate to reproduce simulation results. Orientational correlations at the interface showed a mild tendency for dipolar aligments pointing toward the vapor phase in ACN-rich solutions; contrasting, in DMSO-rich mixtures, the preferential orientations looked mostly parallel to the interface. Close to graphene plates, the local scenarios reverse and local concentrations of DMSO are larger than the one observed in the bulk. Dynamical results reveal that the characteristic time scales describing orientational relaxations and residence times at the interfaces stretch as the concentration of ACN diminishes. For liquid/air interfaces residence times for ACN were found to be larger than those for DMSO. A classical treatment for the predictions of the C-H stretching band of the IR peaks in the bulk and at the interfaces reveals shifts that agree with experimental measurements.